Rainbow daycare / Radin Noor Suzilaazwa Farawati Radin Narawie … [et.al.]. - Radin Narawie, Radin Noor Suzilaazwa Farawati; Lahman, Nurhasninabila; Sharkawi, Norhanifah; Roslan Jeffery, Siti Nur Nabilah; Dalang, Erwin Ashley (2014)
Rainbow Daycare is a full-service nursery dedicated to consistently provide a high customer satisfaction. Our business is in the form of partnership. Each partner has contributed an agreed amount of capital as stated in our agreement. Rainbow Daycare provides early formal education to the clients from the first moment they enter our nursery despite doing our responsibilities of taking care of their welfare. Our nursery shall be located at Lot 80, Lorong 2, Jalan Muda Hashim, 93400 Kuching, Sarawak. All partners will participate in managing the business. We have agreed that Radin Noor Suzilaazwa Farawati Binti Radin Narawie is the General Manager, Nurhasninabila Binti Lahman is the Marketing Manager, Norhanifah Binti Sharkawi as the Operation Manager, Siti Nur Nabilah Binti Roslan Jeffery as the Administration Manager and finally, Erwin Ashley Dalang as the Financial Manager.